IMPLEMENTASI KEBIJAKAN PUBLIK PENGEMBANGAN EKONOMI KREATIF DAN PEMBERDAYAAN MASYARAKAT DI PASAR TRADISIONAL MUNENG KABUPATEN PROBOLINGGO - Yunaz Farada Yoga; Mastina Maksin (JURNAL KATARSIS, 2026)
The main problem in developing the creative economy at Muneng Market in Probolinggo Regency is the low competitiveness of traditional business actors due to minimal digital literacy and limited infrastructure, causing them to be marginalised by modern market expansion. This study aims to analyse the implementation of creative economy development policies in strengthening the economic and social functions of the traditional market and identifying its supporting and inhibiting factors. The research methodology employed a descriptive qualitative approach with in-depth interviews with five traders and five buyers selected through incidental sampling, direct observation of market activities, and documentation studies. The findings show that creative economy development at Muneng Market has contributed to increasing traders’ income, creating new job opportunities, and strengthening local identity through innovation in culinary, fashion, and recycled craft products. Muneng Market also maintains a robust social function as a community interaction space that strengthens personal relationships between traders and consumers. However, policy implementation still faces serious obstacles including low utilisation of digital technology, minimal youth participation, and suboptimal cross-sector collaboration. In conclusion, the creative economy transformation in traditional markets is incremental and requires integrated policy strengthening. This research contributes a participatory analysis model that connects economic, social, and institutional dimensions in developing traditional markets based on the creative economy.